Ekofeminisme: Teori dan Gerakan - siti Fahimah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2017)
Issues or discourses on woman is always interesting for those who deal with the gender equality. Ecofeminism emerges to optimize women’s role by placing great emphasis on ecological issues. Ecofeminism holds the theory that there are differences in nature between man and woman, from the state of their creation by God to the role they play in daily life. Ecofeminism is a movement tackling the problem of female subordination by emphasizing the subordination of ecosystem to human interests. Women naturally love beauty and preservation. Their femininity motivates them to preserve the nature. Ecofeminism utilizes femininity to encourage nature preservation and to prevent any injustice to the nature. The common denominator of ecofeminists is a belief that the energy of femininity has a potential good effect on the preservation of the nature and the conservation of the earth which both men and women occupy. Ecofeminism can also explain clearly that hypermasculinism has its role in causing serious damage to the ecosystem. With the ecofeminism theory, women promote a movement to save the nature.